2010
DOI: 10.1175/2009mwr3119.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two-Way Air–Sea Coupling in High and Low Wind Speed Regimes

Abstract: A recent advance in the Coupled Ocean-Atmosphere Mesoscale Prediction System (COAMPS) is described and used to study two-way air-sea coupling and its impact on two different weather scenarios. The first case examines the impact of a hurricane-induced cold ocean wake on simulated changes in the structure of Hurricane Katrina. The second case investigates the effect of wind-and current-induced island wakes and their impact on the local electromagnetic (EM) and acoustic propagation characteristics in the Southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 31 publications
3
79
1
Order By: Relevance
“…Details about the atmospheric model can be found in Hodur (1997) and Chen et al (2003), and the application of the coupled model has been given by Chen et al (2010); Jensen et al (2011). COAMPS was also used in a fully coupled configuration for the simulation of a 2009 MJO event by Shinoda et al (2013a).…”
Section: Coupled Ocean-atmospheric Mesoscale Predic Tion System (Coamps)mentioning
confidence: 99%
“…Details about the atmospheric model can be found in Hodur (1997) and Chen et al (2003), and the application of the coupled model has been given by Chen et al (2010); Jensen et al (2011). COAMPS was also used in a fully coupled configuration for the simulation of a 2009 MJO event by Shinoda et al (2013a).…”
Section: Coupled Ocean-atmospheric Mesoscale Predic Tion System (Coamps)mentioning
confidence: 99%
“…The Coupled Boundary Layer Air-Sea Transfer (CBLAST) field program (Black et al, 2007) processes (e.g., Bao et al, 2000;Bender et al, 2007;Chen et al, 2007Chen et al, , 2010. The coupling to an ocean-circulation model can improve the storm intensity forecast through a more realistic representation of storm-induced cooling in the upper ocean and sea surface.…”
Section: Tropical Cyclone Prediction Using Coamps-tc B Y J a M E S D mentioning
confidence: 99%
“…The COAMPS-TC system is composed of data quality control, analysis, initialization, and forecast model subcomponents (Doyle et al, 2011) The COAMPS-TC system has the capability to operate in a fully coupled air-sea interaction mode (Chen et al, 2010Doyle, et al, 2011) Charnock parameter (Moon et al, 2004) that is a function of wave age and wind speed. A sea spray parameterization (Fairall et al, 1994(Fairall et al, , 2009Bao et al, 2011) In a seminal study, Powell et al (2003) analyzed data from GPS dropwindsondes deployed from aircraft into hurricanes; they found that the mean wind Both surface drag and sea spray processes play major roles in regulating energy exchange at the air-sea James D. Doyle (james.doyle@nrlmry.navy.mil interface.…”
Section: Coamps-tc Descriptionmentioning
confidence: 99%
“…Pullen et al, 2006Pullen et al, , 2007Chen et al, 2010;Sandery et al, 2010;Warner et al, 2010;Renault et al, 2012;Carniel et al, 2016;Ličer et al, 2016;Bruneau and Toumi, 2016) and operational applications (e.g. Pellerin et al, 2004;Smith et al, 2013;Durnford et al, 2017) to improve the representation of feedbacks in simulations and predictions of the Earth System.…”
Section: Introductionmentioning
confidence: 99%